2019
DOI: 10.33110/cimexus140107
|View full text |Cite
|
Sign up to set email alerts
|

Youth Empowerment as Catalyst for Sustainable Development in Nigeria

Abstract: The field of youth development sits at the frontier of new opportunities for research and practice. Likewise, sustainability of development has remained an area of interest and attracted debates among academia. In advanced economies, development has been successfully sustained over a long period of time but has proofed difficult in developing economies. Though different strategies to empower youths have been put in place in Nigeria, the resulting effects are not sustainable with the rate of poverty and unemplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…The results of the study showed that the first hypothesis was rejected, which means that community empowerment does not affect the mobilization of economic resources, which is in line with research conducted by (Jegede et al, 2019) and(McDonald et al, 2014) where in their study it was found that various strategies were carried out in empowering youth in Nigeria but were not successful due to poor policy implementation. In this study, community empowerment on economic resources in the tourist village of Sudaji must be carried out optimally and in a targeted manner as an effort to restore economic conditions and the level of welfare of underprivileged communities.…”
Section: Discussion the Effect Of Community Empowerment On The Mobili...supporting
confidence: 69%
“…The results of the study showed that the first hypothesis was rejected, which means that community empowerment does not affect the mobilization of economic resources, which is in line with research conducted by (Jegede et al, 2019) and(McDonald et al, 2014) where in their study it was found that various strategies were carried out in empowering youth in Nigeria but were not successful due to poor policy implementation. In this study, community empowerment on economic resources in the tourist village of Sudaji must be carried out optimally and in a targeted manner as an effort to restore economic conditions and the level of welfare of underprivileged communities.…”
Section: Discussion the Effect Of Community Empowerment On The Mobili...supporting
confidence: 69%
“…Studies have found that entrepreneurial competencies such as opportunity recognition has positive effect on youth empowerment or self-employment (Alabi, Sanya & Adekanmbi, 2021;Gill, Aftab, Rehman & Javaid, 2019;Mbah & Okeke, 2020;Omeje, Jideofor & Ugwu, 2020;Pettifor, Wamoyi, Balvanz, Gichane & Maman, 2019). However, other studies like Jegede, Irewole and Dada (2019) found that entrepreneurial programs have not yielded much positive outcomes due to high rate of poverty and unemployment in Nigeria. Yahaya, Inuwa and Hamza's (2021) study in Northeast argued that youths' enrollment in training programmes may be poor without parents' encouragement and that acquisition may not lead to enterprise creation.…”
Section: Problem Statementmentioning
confidence: 99%
“…It is argued in literature that, one of the most important factors in realizing the 2030 Agenda is ensuring youth participation through the means of policy implementation (Jegede et al, 2019). Supporting the execution of pertinent initiatives to foster young people's potential as change agents and engaged citizens for peace and development falls under this category (Jegede et al, 2019). To fully realize the demographic dividend in the subregion, many strategies are needed.…”
Section: Introductionmentioning
confidence: 99%